Psychiatric disorders and psychiatric consultation in a general hospital: A case- control study - Smaira, Sumaia Inaty [UNESP]; Kerr-Corrêa, Florence [UNESP]; Contel, José Onildo B. (EDITORA SCIENTIFIC, 2003)
Introduction: Psychiatric consultation (PC) has been considered an efficient tool to develop research, to track and to give assistance benefiting patients, health professionals and the institution. However, it has not been much used in Brazil. Although 30 to 50% of general hospital (GH) inpatients may present a psychiatric disorder, only 1 to 12% of them are referred to assessment. The aims of this study were: to assess mental disorders in a GH; to identify which of these patients are sent to psychiatric care; to verify alleged reasons for referral to psychiatric consultation, and to examine the relationship between PC and psychiatric learning (during medical school and residence). Methods: A case-control patient study was conducted (47 cases and 94 controls) to analyze in detail the following variables: socio-demographic; clinical; degree of information (about the disease and diagnostic/therapeutic procedures), and relationship between patient and health team. Psychiatric diagnoses were made according to the ICD- 10 criteria. The Self Report Questionnaire (SRQ), the CAGE and Brief Psychiatric Rating Scale (BPRS) were used as well as a specifically designed questionnaire to collect clinical and demographic data. Results: Behavioral alterations, either of elation or of depression, were the main for requesting a PC; 95.8% of the cases and 27.7% of the controls had a mental disorder. Organic mental disorders and alcohol-related disorders were the most frequent diagnoses in group I (cases), while anxiety, depressive and alcohol-related disorders were predominant in group II (controls). Control group patients were better informed and more able to establish an appropriate relationship with the health team than case patients. The logistic regression showed CAGE-positive patients having 12.85 times greater risk of being referred to PC, followed by unemployed patients (2.44 times more PC referrals). Discussion: The SRQ and CAGE were quite useful in the screening of possible patients and might be important for medical students to learn and use as generalists. Further research is needed to verify if and how the newly-established service will improve the diagnostic and treatment skills of our students.
Keywords: Case- control study; General hospital; Psychiatric consultation; Psychiatric disorders; adult; alcoholism; anxiety disorder; case control study; clinical article; controlled study; depression; female; general hospital; human; male; mental disease; organic psychosyndrome; patient referral; psychiatric diagnosis; questionnaire; rating scale; self report; Adult; Case-Control Studies; Female; Hospitals, General; Humans; Male; Mental Disorders; Middle Aged; Multivariate Analysis; Psychiatric Department, Hospital; Referral and Consultation